2014
DOI: 10.1080/07359683.2014.936291
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of and Attitudes Toward Direct-to-Consumer Prescription Drug Advertising Among Young Adults

Abstract: This study examines awareness and knowledge of and attitudes toward direct-to-consumer (DTC) prescription drug advertising among young adults between 18 and 24 years of age. The study finds that young adults are not as aware of prescription drug advertising as older consumers, however, they are aware of specific heavily advertised drugs, especially those for allergy medications, birth control, and sleep aids. Young adults hold mixed to negative views about advertising in general, and they do not view DTC presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The women's generally critical tone in their engagement with these DTC advertisements is consistent with literature indicating that consumers can be active, skeptical viewers of such ads (Alperstein, 2014;Arney et al, 2013;Bell et al, 2010;Joseph et al, 2008). In addition, it is also quite likely that this critical tone was, in part, a product of our recruitment strategy and our method of data generation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The women's generally critical tone in their engagement with these DTC advertisements is consistent with literature indicating that consumers can be active, skeptical viewers of such ads (Alperstein, 2014;Arney et al, 2013;Bell et al, 2010;Joseph et al, 2008). In addition, it is also quite likely that this critical tone was, in part, a product of our recruitment strategy and our method of data generation.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, other researchers have found that DTC drug advertisement spending and/or exposure was associated with increased visits to physicians, including for the purpose of inquiring about, requesting, or attaining a medication (Bell, Taylor, & Kravitz, 2010;Iizuka & Jin, 2005;Joseph, Spake, & Finney, 2008). At the same time, researchers have highlighted that consumers are skeptical or sometimes critical of the information presented in DTC drug advertisements, and that individuals pay varying levels of attention to and have diverse types of engagement with these advertisements (Alperstein, 2014;Arney, Street, & Naik, 2013;Bell et al, 2010;Joseph et al, 2008).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, across this time period there was an increase in the number of DTCA promotional pieces submitted to FDA (as required by FDA regulations that state that prescription drug advertising and promotional labeling must be submitted when it is first disseminated; Kiester, 2007Kiester, , 2012. Although exposure to DTCA remains high (e.g., Alperstein, 2014;Kantar Media, 2013) it is possible that some participants were relying on their impressions of DTCA they had seen in the past rather than more recent advertising. These findings should be replicated and expanded upon in a survey focused on consumers' attitudes regarding DTCA.…”
Section: Discussionmentioning
confidence: 93%
“…This corresponds with the high level of exposure to DTC advertising that individuals reported during this time period. [ 13 – 14 ] FDA conducts surveillance in a variety of ways: through surveillance at medical conventions, review of promotional pieces submitted via FDA Form 2253, and review of submissions of complaints. [ 15 ] FDA may not be able to review every submission because of the sheer volume; however, these data can help FDA allocate resources more efficiently.…”
Section: Discussionmentioning
confidence: 99%